MA CHIAVELLI'O VALDOVAS:DORYBIŲ GALVOSŪKIS. - universiteto, Vilniaus (Problems / Problemos, 2018)
The article deals with the attitude of Nicollò Machiavelli towards virtues and its political meaning explained in his famous work The Prince. Philosopher discusses the meaning of virtues in different stages of his reasoning. He makes partial conclusions at each stage and leads to the final conclusion, which states that virtues are harmfull for the prince, while the deceptive appearance of virtues is most useful. The context of classical political philosophy allows to demonstrate that Machiavelli's proposal to use deception of virtues equates to a perfect injustice. It can be concluded that Machiavelli breaks radically with the Platonic tradition of political philosophy and starts creating a new tradition on the grounds of ideas of ancient sophists about human nature and politics.